AVALIAÇÃO DO CONTROLE INTERNO DE MUNICÍPIOS SOB JURISDIÇÃO DO TRIBUNAL DE CONTAS DE MATO GROSSO DO SUL - Marcelo Pereira da Silva (2023)
Based on studies on the concepts, principles and norms of internal control, this project aimed to investigate the aspects of compliance of the current structure, mode of operation and performance of the internal control bodies of municipalities in Mato Grosso do Sul, discussing its relevance as an instrument for improving public administration, aimed at the realization of the rights and guarantees of the administered – users (effectiveness of governance) and legitimacy of the State (governability). The internal control structure of municipalities under the jurisdiction of the Court of Auditors of Mato Grosso do Sul was selected, evaluating its existence, whether it is necessary and whether it is sufficient to achieve its constitutional and legal objectives. The proposed research has a descriptive character and emphasis on quantitative approaches, using the method of document analysis in which it presents a quantitative description, based on the study of a sample of documents selected to meet the proposed objective. The data were collected through Government Accountability processes made available to the State Court of Accounts. The municipalities selected for this research were the four with the highest annual budget and the four with the lowest annual budget in the State of Mato Grosso do Sul. The results showed that the internal control systems of the municipalities are minimally systemic and in an embryonic stage. In terms of human resources, they presented difficulties in relation to compliance with legislation, staff turnover and participation in the forwarding of accountability or responses to court summonses. Regarding preventive, detective, corrective and directive controls, such as laws and regulatory standards, inspections, audits, among others, they are inefficient, inefficient or even do not have control actions. In terms of active fiscal transparency, it was evidenced that internal controls still do not meet the requirement that all information be widely disseminated and have the participation of the central body of the system. Finally, it is observed that deficiencies in internal control have influenced the efficient use and application of public resources.